Permanent health education: a possibility to improve work in a Technical School of the Unified Health System? (Research, Society and Development, 2020)
This article aims to present a proposal for improvement on processes of Permanent Health Education (EPS) for teachers and direction of a Technical School of the Unified Health System (ETSUS). This is an action research, with qualitative approach, developed between June and November 2019 at the Nurse Izabel dos Santos Technical Training School (ETIS), located in the city of Rio de Janeiro. The methodological route was composed of three phases: exploration, planning and execution. The proposal was based on the Wheel of Conversation method, as this is a method that works with the collective. The study contributed to the updating and expansion of the knowledge of the ETIS teaching and management team about EPS, contributing and promoting changes in actions and work process. This proposal is expected to have a transformative character for the daily work, management and workers, improving the quality of training offered at ETIS.